The Impact of Financial Sector Development on Foreign Direct Investment: An Empirical Study on Minimum Threshold Levels - Tsaurai, Kunofiwa; Makina, Daniel (Journal of Economics and Behavioral Studies, 2018)
Using panel data of 21 emerging economies, the paper investigates the financial sector development threshold levels that would influence foreign direct investment (FDI) inflows. The threshold levels we identified are 41.27% of stock market capitalization for stock market turnover, 53.55% of gross domestic product (GDP) for stock market value traded, 121.53% of GDP for stock market capitalization, 114.43% of GDP for domestic credit to private sector by banks, 144.06% of GDP for domestic credit provided by financial sector, 0.22% of GDP for outstanding domestic private debt securities and 41.26% of GDP for outstanding domestic public debt securities. Our results show that higher stock market and banking sector development above the threshold level positively and significantly influence FDI inflows whilst the influence of lower stock market and banking sector development on FDI inflows was weak and not significant. Levels of private bond market development equal to or greater than the threshold level are found to have a positive but non-significant impact on FDI inflows whilst private bond market development levels less than the threshold have a weaker positive and non-significant influence on FDI inflows. On the other hand, public bond market development levels equal to or greater than the threshold level negatively influenced FDI inflows whilst levels of public bond market development less than the threshold positively but non-significantly attracted FDI inflows into emerging markets.